Engorde de cuyes mejorados (Cavia Porcellus) con bloques nutricionales a base de morera (Morus alba), botón de oro (Tithonia diversifolia) y caraca (Erythrina smithiana)en la Finca "La María" Mocache Provincia de Los Ríos, 2012. - Inte Saquinga, José Eduardo (2013)
The research was carried out at the Experimental Farm "La Maria", owned by the State Technical University Quevedo (UTEQ), located at km 7 1 /2 of the way Quevedo-Mocache; Province of Los Rios, whose geographical location of 1 6 '23 "south latitude and 79 º 29'22" W and a height of 73 meters. The investigation lasted 56 days. Four treatments were evaluated: T1 = Control balanced (block), T2 = block-based nutritional mulberry (30%), T3 = blockbased nutritional Buttercup (30%) and T4 = block-based nutritional caraca (30 %). Using 48 male guinea pigs 20 days of age with an average weight of 296 g, we applied a randomized complete design (DCA) with six replicates; the experimental unit consisted of two animals. We applied the multiple range test of Tukey (P ≤ 0.05). The variables were: nutritional block consumption, weight gain, feed conversion, carcass weight and carcass yield. The profitability of the treatments were determined using the cost-benefit ratio. Nutritional intake block was not affected (P> 0.05) by the inclusion of tropical shrub forage. However most (P <0.05) weight gain, live weight, feed conversion, carcass weight, carcass yield, and profitability, log T2 treatment (6.33 g animal-1 d-1, 655 , 83 g, 3.07, 465.50 g, 71% and 31,20%) respectively. Keywords: shrubs, fodder, food, block, fattening, guinea pigs